The Effect of Using a Heat Collection Filter on the Efficiency of Heat Absorption from the Flame of LPG Gas Fuel - Akhmad Farid; Gatot Soebiyakto (Widyagama University of Malang, 2023)
One of the uses of heat from fuel combustion is for the needs of cooking activities. The heat from the combustion reaction heats the surface of the pan, this occurs in the process of heat transfer by convection on the surface of the pan. The rooting reaction of LPG fuel produces a flow of combustion gas with a high flow speed. This will have the consequence that the heat wasted is very large while the absorbed is very small in the process of heating the surface of the pan. To increase heat absorption by the surface of the pan can be done by inhibiting the flow when the fire touches the surface of the pan. This study will examine how the effect of using a heat collection filter on the heat absorption efficiency of the flame of LPG fuel gas and aims to compare the heat absorption efficiency of a fuel gas flame using a heat collection filter with no heat collection filter (conventional). This study uses independent variables in the form of heat absorption without a heat collection filter and with a heat collection filter, as well as variations in LPG gas flow capacity. While the dependent variable observed is the heating time to obtain heat absorption efficiency. The results showed that convection heat absorption using a heat collection filter has a higher efficiency than without using a heat collection filter at various LPG gas flow capacities